Answered

Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Simplify the expression.
1. (2z³)³

Simplify the expression.
2. (-8ab)²

Simplify the expression.
3. 6 (x³)²


Sagot :

AyaZ
[tex] 1. (2z^3)^3=8 z^{9} [/tex]
[tex] 2. (-8ab)^2=64 a^{2} b^{2} [/tex]
[tex] 3. 6 (x^3)^2=6 x^{6} [/tex]
2^3z^9
A for question 1=8z^9

(-8ab)^2
(-8^2a^2b^2)
A for question 2=64a^2b^2

6 (x^3)^2
6 x^6
6x^6

Enjoy!=)